A NEUROSCIENCE STUDY OF WEAK LEARNERS’ THINKING WHILE SOLVING MATHEMATICAL PROBLEMS - Wan Norliza Wan Bakar (Journal of Islamic, Social, Economics and Development, 2024)
Mathematical problem-solving is among the most difficult kinds that mathematics learners encounter. As a result, this issue has attracted lots of researchers over the past 50 years. Mathematical problem solving requires a few steps of comprehension followed by graphical presentations and then the strategies used. Mathematical problem-solving performance has been associated with some general cognitive resources such as working memory, long-term memory, and inhibitory skills. This paper aims to study the neuroscience of weak learners while solving mathematical problems. 3 students of Pra Pendidikan Tinggi March - August 2023 were selected. The students were required to solve mathematical word problems while they were videotaped. Respondents were then interviewed, and the interview session was audiotaped to be transcribed. The transcribed data were then simplified and tabulated together with students' written work and were analyzed to determine the weak learner’s perception and problem-solving strategy analysis showed that weak learners were unable to solve mathematical problems due to encoding failure or lack of retrieval cues. This occurs as a result of improper long-term memory storage of the concept.